Extracellular histones cause intestinal epithelium injury and disrupt its barrier function in vitro and in vivo. (15th March 2022) - Chen, Chanjuan; Lin, Ziqi; Zhang, Xiaoxin; Zhang, Xiaoying; Cheng, Zhenxing; Jin, Tao; Liu, Tingting; Deng, Lihui; Guo, Jia; Wang, Guozheng; Xia, Qing
Abstract: Extracellular histones are cytotoxic to various cells and have been extensively proven a vital mediator of multiple organ injuries. However, the effect of extracellular histones on the intestine remains largely unknown. This study aimed to clarify the effect of extracellular histones on the intestine. IEC-6, a cell line of rat small intestinal epithelial crypt, and C57BL/6 or ICR mice were treated with histones. The IEC-6 cells treated with histones from 20 μg/mL to 200 μg/mL for 0−24 h displayed a decline of cell viability and an increase of cell death in a concentration- and time-dependent manner. Moreover, histones (100 μg/mL) induced IEC-6 apoptosis through activating caspase 3 and necroptosis through up-regulation of receptor-interacting serine/threonine protein kinase 1 and 3 (RIPK1 and RIPK3), phosphorylated mixed-lineage kinase domain-like protein (p-MLKL) along with the decrease of caspase-8. Histones treatment disturbed zonular occludens 1 (ZO-1) expression and increased permeability of IEC-6 cell monolayer. In vivo, histones 50 mg/kg injection caused mice intestinal edema, loss apex of villus, epithelial lifting down the sides of the villi, and increased neutrophil infiltration. Elevation of serum intestinal fatty acid binding protein (I-FABP), d -lactate, or Diamine oxidase (DAO) and loss of tight junction protein, ZO-1, at 3 h and 6 h after histones injection strongly indicated severe intestinal epithelium injury, which led to increased permeability of the intestine. In conclusion, extracellular histones cause intestinal epithelial damage via direct cytotoxicity. Consequently, intestinal epithelial tight junction and barrier integrity are disrupted, which may play pivotal roles in diverse diseases.